Gastrointestinal Schwannoma: An Unusual Colonic Lesion Mimicking Adenocarcinoma - Brent K Wilde; Jenna-Lynn Senger; Rani Kanthan (Canadian Journal of Gastroenterology)
Gastrointestinal schwannoma is a rare, benign pathological entity that can mimic colonic adenocarcinoma and cause diagnostic dilemmas for treatment. A case of a 68-year-old woman with colonic adenocarcinoma who was discovered to have an incidental synchronous bowel lesion that proved to be a gastrointestinal schwannoma and not a synchronous adenocarcinoma is described. Gastrointestinal schwannomas are uncommon in the colorectal region; they are most often located in the stomach. These spindle cell lesions are distinct from gastrointestinal stromal tumours because the tumour cells have a distinct immunophenotype, with strong diffuse positivity for S-100, glial fibrillary acidic protein and vimentin, and corroborative negative staining of CD34, CD117 and smooth muscle markers. Accurate diagnosis and recognition of this benign entity is, therefore, of immense clinicopathological value for accurate planning of therapeutic strategies.